A study on the important design considerations for wheelchair accomodation within a private environment - Ruiz, Rebecca J.; Florendo, Raquel Baltazar (1991.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BID)--University of the Philippines Diliman.
Keywords: Barrier-free design -- Philippines